2019
DOI: 10.3389/fimmu.2019.00804
|View full text |Cite
|
Sign up to set email alerts
|

Notch-Mediated Tumor-Stroma-Inflammation Networks Promote Invasive Properties and CXCL8 Expression in Triple-Negative Breast Cancer

Abstract: Stromal cells and pro-inflammatory cytokines play key roles in promoting the aggressiveness of triple-negative breast cancers (TNBC; Basal/Basal-like). In our previous study we demonstrated that stimulation of TNBC and mesenchymal stem cells (MSCs) co-cultures by the pro-inflammatory cytokine tumor necrosis factor α (TNFα) has led to increased metastasis-related properties in vitro and in vivo . In this context, elevated release of the pro-metastatic chemokines CXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 71 publications
2
49
0
Order By: Relevance
“…DNER, atypical ligand of the Notch1 pathway, was initially found to be highly expressed in Purkinje neurons and plays a key role in cerebellar development 25,26 . Furthermore, the Notch pathway is involved in carcinogenesis and promotes the proliferation and malignant progression of various tumours [27][28][29] . Until now, the role of DNER in cancer has remained controversial, and the function of DNER may vary according to cell type.…”
Section: Discussionmentioning
confidence: 99%
“…DNER, atypical ligand of the Notch1 pathway, was initially found to be highly expressed in Purkinje neurons and plays a key role in cerebellar development 25,26 . Furthermore, the Notch pathway is involved in carcinogenesis and promotes the proliferation and malignant progression of various tumours [27][28][29] . Until now, the role of DNER in cancer has remained controversial, and the function of DNER may vary according to cell type.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of CAF‐secreted IL‐6 induced tumor immunosuppression by recruiting MDSCs and upregulating PD‐L1 expression, impairing the efficacy of anti‐PD‐L1 immunotherapy against hepatocellular carcinoma (HCC), and IL‐6 blockade increased the efficacy of PD‐L1 treatment . Interestingly, tumor‐associated stromal cells/CAFs themselves also expressed PD‐L1 to suppress CD8 + antitumor immune responses in response to the inflammatory secretome from human colon cancer cells, and pre‐inflammatory cytokine TNFα and IL‐1β induced CXCL8/CCL5 secretion in the co‐culture of CAFs and triple negative breast cancers , suggesting that the inflammation also regulates the immunological response of CAFs/stromal cells in the TME. In addition, CAFs in HCC regulate the survival and activation of neutrophils through the IL‐6–signal transducer and activator of transcription (STAT) 3–PD‐L1 signaling pathway and consequently affect the function of T cells .…”
Section: Regulation Of Tumor Immune Response By Cancer‐associated Fibmentioning
confidence: 99%
“…Recent studies have shown that the cell surface adhesion receptor CD44 is a key positive regulator of PD-L1 expression in TNBC and non-small cell lung cancer (NSCLC) (Kong et al, 2019). The Notch-mediated tumorinterstitial-inflammatory network promotes TNBC invasiveness and CXCL8 expression (Liubomirski et al, 2019). High expression of UBE2C is a potential factor for poor prognosis of TNBC.…”
Section: Enrichment Analysis Of Degs Ppi Network Of Olibanum-treated mentioning
confidence: 99%